What does TikTok have to do with it? Experiences of Young Adults with Social Media and Life Satisfaction: A Qualitative Analysis of Influences - Espinoza, Janet; Weekes, Arthalia (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
This qualitative study investigates the impact of TikTok usage on the life satisfaction and its contribution towards self-actualization of young adults aged 18-25. Adopting a phenomenological approach, the research explores the experiences and perceptions of TikTok engagement and its relation to the life satisfaction of five young adults. Six main themes emerged for the analysis: 1) Love & Belonging, 2) Influence, 3) Life Satisfaction, 4) Self-Esteem and Identify, 5) Mood, and 6) Risks and Challenges. These findings uncover various aspects of TikTok use, such as content consumption patterns and emotional responses, offering insights into the nuanced ways TikTok influences young adults’ perceptions of their lives and contribute to a deeper understanding of the relationship between the platform engagement and life satisfaction. Furthermore, this research underscores the importance of social workers’ role in advocating for ethical social media practices and clinical interventions tailored to address the impacts of social media on the overall wellbeing of young adults.